Performing Environments Site-Specificity in Medieval and Early Modern English Drama - Bennett, S.; Polito, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This ground-breaking collection explores the assumptions behind and practices for performance implicit in the manuscripts and playtexts of the medieval and early modern eras, focusing on work which engages with performance-oriented research.
Keywords: Performing arts; Theater; Literature; Architecture; British literature; Theater—History.; Performing Arts; Theatre and Performance Studies; Literature, general; Architecture, general; British and Irish Literature; Theatre History